Method of operative diagnostics of fault-tolerant systems of power supply of aircraft - Захарченко, В. П. (Proceedings of National Aviation University (archive), 2002)
The method of operative diagnostics of fault-tolerant systems of electric power supply of aircraft and method of its realization is given. The algorithm of a flexible bounce search program, implemented on the basis of the use of information about the signs of normal functioning, failures and the mutual influence of elements of fault-tolerant complexes, is considered.